Reliability analysis and pre-sizing of a switched-inductor-capacitor-based quadratic boost converter using genetic algorithm - Divya Navamani J; Lavanya A; Pradeep Vishnuram; Mohit Bajaj; Vojtech Blazek (Results in Engineering)
This paper analyses various performance metrics of a Switched-inductor/capacitor-based Quadratic boost converter (QBSIC). In this topology, a switched inductor/capacitor (SIC) cell is incorporated in the second inductor of the quadratic boost converter to enhance the gain ratio of the topology. This paper mainly concentrates on the various performance studies such as dynamic, reliability and cost study of the topology rather than the steady-state analysis. High gain, efficiency, reliability and low cost are the prominent attributes endorsed through the analysis discussed in this paper. The reliability study is analysed using the reliability tool, the military handbook MIL-HDBK-217 and Mean to Time Failure (MTTF) is compared in ground mobile and airborne environmental conditions. This tool is compatible and provides a standardized procedure for determining the reliability of electronic equipment. Furthermore, the cost analysis of the topology for expected lifetime of 5 years is performed because it is the most important criterion for choosing a topology for any application. From analysis, it is noted that the cost of QBSIC converter is 1.7 % less than the converter considered for comparison. In the process of product development, the pre-sizing approach is the most essential step to optimize the size and performance of the product. To achieve the optimum switching frequency of the topology, a Genetic Algorithm (GA) is employed. To highlight the superiority of the proposed topology, it is compared with a switched inductor-based converter, and the results are presented. The rating of xenon lamps in passenger and heavy-duty vehicles ranges from 35 W to 55 W. Finally, a 50 W prototype is tested on a laboratory scale and results are presented for validation. For 0.4 duty cycle, it gives the gain of 5 and it is validated successfully.